EFICIÊNCIA DOS PRINCIPAIS MÉTODOS DE IMPERMEABILIZAÇÃO EM ESTRUTURAS DE CONCRETO (REMUNOM, 2025)
Waterproofing concrete structures is essential for the durability of buildings, preventing infiltration and structural pathologies that may compromise their integrity. This study aims to compare the main waterproofing methods, analyzing their efficiency, durability, cost-effectiveness, and suitability for different structural and climatic conditions. The research was conducted through a literature review, The results indicate that membrane, rigid, and flexible waterproofing methods have distinct characteristics, with the choice of system depending on the specificities of the construction. Membrane methods, such as asphalt sheets and PVC, demonstrate high immediate efficiency, while rigid methods, such as crystallization and modified cements, stand out for their durability. Flexible systems, based on polyurethane and acrylic polymers, offer greater adaptability to structures subject to movement. The comparative analysis highlights that the selection of the ideal method should consider not only initial costs but also maintenance and compliance with current technical standards. It is concluded that the appropriate choice of waterproofing system is essential for the longevity of buildings, requiring investment in professional training and the correct application of materials. Keywords: Waterproofing; Concrete; Construction methods; Structural pathologies